LITERARY TEACHING AND ITS CONSTRAINTS: PARADIGMS AND PROBLEMS - Ali Mustofa (University of Kuningan, 2016)
The paper will explore the nature of the literary teaching and its constraints. In language teaching, literary teaching has been promoted influential and approved effective to encourage the students’ character building in terms of some issues: historical, philosophical, cultural, social, and psychological contexts. Historically, literary teaching will provide students and learners of the ancients’ way of life and learn from the best in the past for their life experience. Some constraints may arise in language teaching due to the cultural and the philosophical boundaries. The constraints may be put into some categories; philosophical, cultural, social, and psychological. To generalize the idea, literary teaching needs efforts to boost the students’ skills to creatively launch themselves to a higher level of thinking order to achieve the goals of literary teaching and the demand of curriculum.Keywords: literary teaching, humanity issues, constraints, critical thinking, competency